Spiritual Communication of Grebeg Maulid Ceremonial Cultural Space in Madiun’s Town Square - Wulandari, Lisa Dwi; Pratiwi, Elsa Intan (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2023)
Culture became a city character that will keep developing through times, Grebeg Maulid of Madiun is one example of developing culture into tourism sites. Madiun’s Government was so intensively introducing Madiun as a religious tourism sites. This research talks about ritual communication presented by the people through cultural space that formed in Madiun’s town square area during grebeg maulid ceremony. Method used in this research is descriptive qualitative with etnographic approach, using Dell Hymes theory for the guidelines. Collected result will talk about communication form of grebeg maulid in madiun’s town square. Study of this research could be a new start for researchers to do deeper research using etnographic method about grebeg maulid. Furthermore, this research will also be an image for the government’s planning in developing culture into tourism sites (religious tourism sites) without losing its meaning.